2018
DOI: 10.1111/chd.12613
|View full text |Cite
|
Sign up to set email alerts
|

Nit-Occlud Lê VSD coil versus Duct Occluders for percutaneous perimembranous ventricular septal defect closure

Abstract: Percutaneous pmVSD closure using either Nit-Occlud Lê VSD Coil or Duct Occluders is feasible, safe and efficacious in selected patients. The main problems of Duct Occluders are unsuitable defect anatomy and device embolization while VSD Coil disadvantages are residual shunt and hemolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 37 publications
5
17
1
6
Order By: Relevance
“…This was the initial study for introducing this device in clinical practice and, therefore, incorporates the learning curve for the operators using this coil. The final closure rates are close to those reported by others [6,9,16,20,21,23,25,29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was the initial study for introducing this device in clinical practice and, therefore, incorporates the learning curve for the operators using this coil. The final closure rates are close to those reported by others [6,9,16,20,21,23,25,29].…”
Section: Discussionsupporting
confidence: 90%
“…Double-umbrella devices are additionally used in VSD without aneurysmal formation and due to the clipping and stenting mechanism, the risk of causing arrhythmias for these types of defects is potentially higher. Nygyen showed that percutaneous pVSD closure using either Nit-Occlud Lê VSD Coil or Amplatzer Duct Occluders is feasible, safe and efficacious in selected patients [21]. The main problems of Duct Occluders are unsuitable defect anatomy and device embolization, while VSD Coil disadvantages are residual shunt and hemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The most feared complication of transcatheter VSD closure is cAVB with a reported incidence of 0-6.4% [7,25,28,30,32] and cAVB after surgical VSD closure has been reported with a prevalence of 1-5% [16,[33][34][35]. More current studies have reported cAVB rates between 1.25 and 1.4% for transcatheter VSD closure as a comparable risk after operation [9,31,[36][37][38][39]. According to our data, we observed only 1/149 (rate 0.7%) patient with cAVB for all different VSD devices investigated during > 6 years of follow-up, which is a lower rate than published data to date for interventional and Fig.…”
Section: Arrhythmiamentioning
confidence: 88%
“…Remarkably, a new small but detectable shunt was again detected in one of our patients with the Nit-Occlud® 3 years after the procedure during pregnancy. This reopening of the shunt might be a result of increased cardiac output and ventricular dilatation during pregnancy [7,9,31,32]. Therefore, residual shunting appears to be related to the device type and location of the VSD.…”
Section: Residual Shuntmentioning
confidence: 99%
See 1 more Smart Citation